A stiff collar can restrict atlantoaxial instability in rheumatoid cervical spine in selected cases. Issue 4 (April 1995) - Kauppi, M; Anttila, P
Abstract : OBJECTIVE--To study the efficiency of a stiff collar in restricting the instability of anterior atlantoaxial subluxation (AAS). METHODS--Twenty two successive patients with an unstable AAS were studied. Lateral view radiographs were taken of the cervical spine in flexion, extension, and neutral positions without a collar, and in full flexion with a custom made stiff collar. RESULTS--The collar restricted more than 30% of the maximal instability of the AAS in 50% of the patients. These patients had significantly shorter atlantoaxial distance in the neutral position than those in whom the collar was not able to restrict the instability. CONCLUSION--A stiff collar can restrict the atlantoaxial instability in selected rheumatic patients with an unstable AAS. Lateral view radiographs of the cervical spine in a neutral position can be used to identify the patients whom the collar will benefit.